2013
DOI: 10.1016/j.jeurceramsoc.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of the thermal expansion of Cr2(Alx,Ge1−x)C phases

Abstract: We report thermal expansion coefficients of the end members and solid-solution compounds in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(62 citation statements)
references
References 64 publications
(87 reference statements)
7
53
1
1
Order By: Relevance
“…The ability to alloy on the M, A, or X site [42,[65][66][67][68][69][70][71] or create artificial superstructures composed of different MAX phases would allow for possible routes to affect/tune electronic, magnetic, and mechanical properties without affecting the inherent atomically laminated structure. In addition, a new family of two-dimensional (2D) materials known as MXenes was recently discovered, realized by etching the A layers from the MAX phase [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to alloy on the M, A, or X site [42,[65][66][67][68][69][70][71] or create artificial superstructures composed of different MAX phases would allow for possible routes to affect/tune electronic, magnetic, and mechanical properties without affecting the inherent atomically laminated structure. In addition, a new family of two-dimensional (2D) materials known as MXenes was recently discovered, realized by etching the A layers from the MAX phase [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, ternary carbide Cr 2 AlC has attracted much attention because of its excellent high-temperature oxidation and hot corrosion resistance [14,[25][26][27], due to preferential formation of continuous protective Al 2 O 3 oxide at high temperatures [15]. Moreover, a small difference in thermal expansion coefficients between Cr 2 AlC and Ni-based alloys makes them along with Cr 2 (Al x ,Ge 1−x )C, potential protective film candidates at high temperature [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Bei et al [17], for example, investigated Ti 2 Al 1−x Sn x C solid solutions and concluded that the addition of low melting elements in the A sublattice of aluminum-containing MAX phases could lead to reduction of oxidationinduced crack healing temperatures. Cabioch et al [18] proposed the partial substitution of Al for Ge in the Cr 2 Al 1−x Ge x C 2 system as a strategy to tune the thermal expansion coefficient in this system. Yu et al [19] investigated Cr 2 (Al,Si)C solid solutions and concluded that partial substitution of Al for Si had positive effects on the strength of the material.…”
Section: Introductionmentioning
confidence: 99%